Redesign UI/UX Website of Professional Certification Institute Using Design Thinking Method and Agile Framework - Rendi Brahma Fahrezi (Eduvest - Journal of Universal Studies, 2024)
Professional Certification Institute (Lembaga Sertifikasi Profesi, LSP) is important in improving the quality of human resources in Indonesia through the provision of training and competency tests in accordance with their fields. For this reason, a medium is needed to promote the services of the Professional Certification Institute in order to reach the Indonesian people widely and online. One of the efforts to improve the promotion of the LSP Ditekindo is to improve the quality of the LSP Ditekindo website. The purpose of this research is to provide recommendations for redesigning and improving the quality of UI/UX, as well as completing information that should be on the LSP Ditekindo website. Researchers applied the Design Thinking method and Agile Framework, and collected data through questionnaires to find out user opinions about the website. The results showed that the Design Thinking method proved to be able to produce a better website redesign in terms of user experience. The Agile Framework method also helps produce a website redesign that is iterative, collaborative, and responsive to user needs. This is evidenced by the results of A/B Testing that has been carried out, where overall Design B or the results of the LSP Ditekindo website redesign were selected and favored by the accession.